2014
DOI: 10.1017/jfm.2014.89
|View full text |Cite
|
Sign up to set email alerts
|

Spanwise-localized solutions of planar shear flows

Abstract: We present several new spatially localized equilibrium and traveling-wave solutions of plane Couette and channel flows. The solutions exhibit strikingly concentrated regions of vorticity that are flanked on either side by high-speed streaks. For several traveling-wave solutions of channel flow, the concentrated vortex structures are confined to the nearwall region and form particularly isolated and elemental versions of coherent structures in the near-wall region of shear flows. The solutions are constructed b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 68 publications
10
67
0
Order By: Relevance
“…Avila et al (2013) found a streamwise-localized relative periodic orbit of pipe flow that closely resembles the transient turbulent puffs of Hof et al (2006). Deguchi et al (2013) and Gibson & Brand (2014) independently found spanwise-localized forms of the periodic EQ7/HVS solution of Itano & Generalis (2009);Gibson et al (2009). Gibson & Brand (2014) also presented a number of spanwise-localized and wall-normal-localized traveling waves of channel flow.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Avila et al (2013) found a streamwise-localized relative periodic orbit of pipe flow that closely resembles the transient turbulent puffs of Hof et al (2006). Deguchi et al (2013) and Gibson & Brand (2014) independently found spanwise-localized forms of the periodic EQ7/HVS solution of Itano & Generalis (2009);Gibson et al (2009). Gibson & Brand (2014) also presented a number of spanwise-localized and wall-normal-localized traveling waves of channel flow.…”
Section: Introductionmentioning
confidence: 91%
“…The mathematical formulation and numerical methods are presented in detail in Gibson & Brand (2014) (GB14); here we present a brief outline. The Reynolds number Re for plane Couette flow is defined in terms of half the relative wall speed, the channel halfheight, and the kinematic viscosity, so that the walls at y = ±1 have velocity ±1 and the laminar flow solution is given by y e x .…”
Section: Computation Of Doubly-localized Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…§3.2 then describes the results of edge-tracking in a variety of geometries aimed at uncovering new ECS. Two already known, albeit now stratified, ECS are repeatedly found -EQ7 and EQ7-1 in the nomenclature of Gibson & Brand (2014). In §3.3 these are continued around in (Re, Ri b ) parameter space, including into negative Ri b (unstable stratification), along with Nagata's (1990) first solution in pCf.…”
Section: Introductionmentioning
confidence: 94%
“…In this sense our use of the word 'localization' is different from that used in recent numerical investigations of fully isolated vortex structures, e.g. Schneider, Gibson & Burke (2010), Deguchi, Hall & Walton (2013) and Gibson & Brand (2014). Similar computations are now presented for larger values of β.…”
Section: Computational Results For the Strongly Nonlinear Vortex/ts Wmentioning
confidence: 91%